Porocarcinoma of the left arm: A report of a rare skin cancer case and literature review. Issue 4 (15th April 2022) - Signorelli, Carlo; Zanella‐Cavallero, Luca; Ranucci, Valentina; Pellicciotti, Antonio; Ruggeri, Enzo Maria
Abstract: Porocarcinoma is a rare type of skin cancer that develops from the intraepidermal ductal part of eccrine sweat glands. It can arise de novo or from poroma ground with high potential for locoregional metastatic spread, morbidity, and mortality. It mostly occurs in elderly patients. Abstract : PC is frequently missed as a differential diagnosis due to its rarity and nonspecific appearance. Our case suggests that early identification and complete excision offer the best chances of feasible recovery even in elderly patients.